Improving the sensory and rheological properties of yogurt using aqueous extract of basil (Ocimum basilicum L.) - Khalil, Isra'a Qassim Mohsen; Hussain, Mahdi Hassan (Journal of Kerbala for Agricultural Sciences, 2022)
This study aims to produce a therapeutic milk product (yogurt) to improve and treat many different digestive problems, using the lactic acid bacteria (Streptococcus thermophilus and Lactobacillus bulgaricus) supplemented with aqueous extract of the plant (basil) with three concentrations of 1%, 3% and 5% [v/v] basil, they were represented by R1, R2 and R3 treatments respectively, as well as the control [C] treatment in which the yogurt was made without any addition. The treatments were stored for 21 days at [5±1] °C. The physicochemical properties were studied, which included measurement [pH, total acidity, syneresis, viscosity, and hardness] and microbiological examinations, as well as sensory evaluation on the first day of manufacture and after 7, 14 and 21 days of cold storage. The results showed that there were no significant differences in pH values immediately after manufacturing for all treatments. As for the percentage of total acidity (TTA), it was close to immediately after manufacturing for all the different yogurt treatments, while during storage, a clear increase in their values was observed for all transactions. Results showed a significant difference in syneresis, viscosity and hardness immediately after manufacturing and during cold storage for all treatments. R1 and R2 treatments improved the viscosity, hardness and syneresis of yogurt. The R2 and R3 treatments recorded the highest numbers of starter bacteria compared to the other treatments. Also, the results showed that the superiority of R2 treatment in the sensory evaluation of the characteristics of taste, flavor, texture and general acceptance.